Generational accounting in Portugal : an assessment of long-term fiscal sustainability and intergenerational inequality - Pinheiro, Jorge (2021)
The social and economic developments in European countries have put pressure on their national budgets and threaten the sustainability of public policies. The traditional fiscal indicators, specifically, the deficit and the debt, which are still used today as guiding tools, have proved to be insufficient, due to their arbitrary nature and short-term focus. In this paper, we resort to an alternative fiscal indicator, known as ‘generational accounting’, which is able to incorporate the future changes in the demographic structure of the population, and their corresponding impact on public accounts. It is also able to evaluate how current fiscal policy affects, not only, current generations, but also future generations. We apply this methodology to assess the long-term fiscal situation of Portugal, and compare the results with those obtained in 1999. In this context, we also explore additional scenarios, as well as additional indicators, in order to provide some robustness to our findings. Our results show that, if the current fiscal policy is not significantly changed, future generations will face a much heavier fiscal burden than current generations.